2015
DOI: 10.1159/000443775
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Traumatic Amputation on β-Trace Protein and β2-Microglobulin Concentrations in Male Soldiers

Abstract: Background: Serum creatinine (SCr) levels are decreased following traumatic amputation, leading to the overestimation of glomerular filtration rate (GFR). β-Trace protein (BTP) and β2-microglobulin (B2M) strongly correlate with measured GFR and have not been studied following amputation. We hypothesized that BTP and B2M would be unaffected by traumatic amputation. Methods: We used the Department of Defense Serum Repository to compare pre- and post-traumatic amputation serum BTP and B2M levels in 33 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…In the same cohort, Little et al . observed no significant changes in BTP or B2M concentration following traumatic amputation, 27 similar to our findings for nontraumatic amputation. The authors hypothesize that an eGFR equation combining cystatin C, BTP and B2M (excluding creatinine) would be most accurate for patients with traumatic amputation because these markers are less influenced by muscle mass.…”
Section: Discussionsupporting
confidence: 91%
“…In the same cohort, Little et al . observed no significant changes in BTP or B2M concentration following traumatic amputation, 27 similar to our findings for nontraumatic amputation. The authors hypothesize that an eGFR equation combining cystatin C, BTP and B2M (excluding creatinine) would be most accurate for patients with traumatic amputation because these markers are less influenced by muscle mass.…”
Section: Discussionsupporting
confidence: 91%
“…1, 2, 12 These findings suggest that eGFR B2M and eGFR BTP , similar to eGFR cys , may be more accurate than eGFR cr in patients with alterations in muscle mass, such as limb amputations, eating disorders, neuromuscular disorders or malnutrition. 13, 14 On the other hand, significant residual associations of cystatin C and B2M but not creatinine with BMI suggests that eGFR cys and eGFR B2M may be less accurate than eGFR cr in obesity.…”
Section: Discussionmentioning
confidence: 99%
“…One found that agents such as propofol (with hepatic first-pass clearance) likely need to be dosed based on theoretical able-bodied weight (i.e., preamputation) rather than postamputation weight (as the full hepatic enzymatic complement is still operational and likely to act on the same fraction of an administered dose). 6 Another study calls attention to the deliberate therapeutic drug level monitoring for a chemotherapeutic agent, 7 as estimated glomerular filtration rates based on serum creatinine clearance postamputation typically overestimate renal function, [8][9][10] influencing dosing. 8 The purpose of this study was to perform a retrospective investigation into the practices surrounding postamputation transition of care medication prescribing patterns at an academic hospital.…”
mentioning
confidence: 99%